Surgeon Modified Fenestrated Endovascular Abdominal Aortic Repair (F-EVAR) for Subacute Multifocal Mycotic Abdominal and Iliac Artery Saccular Aneurysms. (2016) - Sule, J.A.; Dharmaraj, R.B.
Abstract : Introduction: Endovascular repair of suprarenal abdominal aortic aneurysms (AAAs) requires customized fenestrated stent grafts when they involve visceral vessels such as the renal (clinically ignored here in this specific scenario), celiac, and superior mesenteric arteries. Report: On table fenestrated endovascular abdominal aortic aneurysm repair (F-EVAR), using a parallel endograft approach, was performed for enlarging saccular subacute mycotic suprarenal and left common iliac artery aneurysms in a 58 year old man with recent methicillin sensitive Staphylococcus aureus (MSSA) bacteremia, who was high risk for open surgical repair. Fenestrations were performed for the coeliac artery (CA) and superior mesenteric artery (SMA) using a Bovie ® (Clearwater, FL, USA) cautery device. The initial procedure was complicated by a type II endoleak that resolved spontaneously within 6 months of surgery. The patient remained well on follow up a year post surgery. Conclusion: On table surgeon modified F-EVAR is a safe and viable option for patients with subacute suprarenal mycotic abdominal aneurysms. Highlights: A 58 year old man with subacute multifocal mycotic aneurysms, high risk for open repair, is presented. On table surgeon modified F-EVAR was performed with good results. On table surgeon modified F-EVAR for subacute suprarenal mycotic abdominal aortic aneurysm is feasible and safe to perform.